Bupleurum chinense DC improves CUMS-induced depressive symptoms in rats through upregulation of the cAMP/PKA/CREB signalling pathway. (10th May 2022) - Chang, Baijin; Liu, Yanru; Hu, Jingting; Tang, Zhishu; Qiu, Zhidong; Song, Zhongxing; Jia, Ailing; Zhang, Yuru
Abstract: Ethnopharmacological relevance: Bupleurum chinense DC. ( B . chinense ) is the dried root of B . chinense, belonging to the Umbelliferae family. B . chinense has been reported since ancient times for its effect of soothing the liver and relieving depression. Additionally, its important role in treating depression, depressed mood disorders and anti-inflammation has been proven in previous studies. However, its specific mechanism of action remains unknown. Aim of the study: The key targets and metabolites of the antidepressant effect of B . chinense were investigated based on the cAMP signalling pathway. The study examined the mechanism for the antidepressant effect of B . chinense by target prediction, analysis of related metabolites and potential metabolic pathways. Materials and methods: A network pharmacology approach was used to predict the antidepressant targets and pathways of B . chinense . A depression rat model was established through the CUMS (chronic unpredictable mild stress) procedure. The depression model was assessed by body weight, sugar-water preference, water maze and enzyme-linked immunosorbent assay (ELISA) indicators (5hydroxytryptamine, etc.). The key metabolic pathways were screened by correlations between metabolites and key targets. Finally, a quantitative analysis of key targets and metabolites was experimentally validated. Results: B . chinense significantly ameliorated the reduction in body weight, sugar-water preference rate and cognitive performance in the water maze experiment in rats with depression induced by CUMS. ELISA, Western blotting (WB) and reverse transcription-polymerase chain reaction (RT-PCR) assays showed that B . chinense significantly improves the expression of protein kinase cyclic adenylic acid (cAMP)-activated catalytic subunit alpha (PRKACA), cAMP-response element-binding protein (CREB) and cAMP activation in the rat brain induced by CUMS. According to metabolic pathway analysis, B. chinense shows an antidepressant effect primarily by regulating the cAMP metabolic pathway. Conclusion: B. chinense upregulated PRKACA and CREB expression and the level of the key metabolite cAMP in the cAMP/PKA/CREB pathway while reducing the inflammatory response to depression treatment. These new findings support future research on the antidepressant effects of B. chinense . Graphical abstract: Image 1 Highlights: Bupleurum chinense DC. could restore the expression of PRKACA, CREB. B.chinense could significantly increase the content of metabolite cAMP. B.chinense could regulate the imbalance of cAMP/PKA/CREB signalling pathway.